Faktor-Faktor yang Mempengaruhi Cash Holdings pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Al Rifqi Arifin; Igo Febrianto (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study investigates the determinants of cash holdings in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2018–2022. Cash holdings play a crucial role in ensuring company liquidity and financial flexibility, especially in industries that require large investments such as the energy sector. The study employs secondary data obtained from annual financial reports of the sampled companies, accessed through official company websites and the IDX portal. A quantitative research approach is used with multiple linear regression analysis to test the effect of several independent variables on cash holdings. The variables examined include firm size, leverage, growth opportunity, profitability, net working capital, capital expenditure, and cash flow. The findings reveal that firm size and leverage both have a negative and significant effect on cash holdings, indicating that larger firms and those with higher debt levels tend to maintain lower levels of cash. Net working capital and capital expenditure are also found to negatively affect cash holdings, suggesting that higher investments in working capital and assets reduce the need for holding large cash reserves. Conversely, cash flow demonstrates a positive effect, highlighting that firms with stronger cash inflows are likely to hold more cash. Growth opportunity and profitability show no significant effect on cash holdings.